Direct and indirect effects of the fungal endophyte Epichloë uncinatum on litter decomposition of the host grass, Schedonorus pratensis - Gundel, Pedro Emilio (2017)
Fil: Gundel, Pedro Emilio. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.